2012
DOI: 10.4253/wjge.v4.i3.96
|View full text |Cite
|
Sign up to set email alerts
|

Typical gastroduodenal endoscopic findings in a Crohn's disease patient in remission stage

Abstract: A 39-year-old patient with Crohn's disease (CD) was referred to our hospital for maintenance treatment of CD. He was diagnosed as having CD of the small and large intestines at 32 years old. He underwent partial resection of the ileum at 35 years old because of ileal perforation. He had received enteral nutritional supplement (1200 kcal/d) and metronidazole preparation (500 mg/d), and was in remission Crohn's disease activity index 73. We performed a routine gastroduodenal endoscopic examination, which reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As we first reported the high incidence of a bamboo-joint-like appearance detected in the stomach of CD patients, 20 2 studies and some case reports suggested the usefulness of a bamboo joint-like appearance for diagnosing CD. 21 , 22 , 24 26 Hirokawa et al showed in their retrospective study that a bamboo joint-like appearance in the upper GIT was detected in 15 of 23 (65.2%) CD patients. 21 Kuriyama et al also showed that there was a high incidence of the bamboo joint-like appearance (28 of 63 [44%]) in CD patients in comparison to that in the patients with UC (5%) or reflux esophagitis (0%).…”
Section: Discussionmentioning
confidence: 99%
“…As we first reported the high incidence of a bamboo-joint-like appearance detected in the stomach of CD patients, 20 2 studies and some case reports suggested the usefulness of a bamboo joint-like appearance for diagnosing CD. 21 , 22 , 24 26 Hirokawa et al showed in their retrospective study that a bamboo joint-like appearance in the upper GIT was detected in 15 of 23 (65.2%) CD patients. 21 Kuriyama et al also showed that there was a high incidence of the bamboo joint-like appearance (28 of 63 [44%]) in CD patients in comparison to that in the patients with UC (5%) or reflux esophagitis (0%).…”
Section: Discussionmentioning
confidence: 99%
“…The authors described that the notch-like appearance and erosions and/or ulcerations had an incidence of 9.9% and 32.1% respectively[ 68 ]. This endoscopic aspect is also described in patients with the disease in remission[ 69 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Kuwaki et al [ 21 ] showed that the BJA in the stomach of a CD patient remained unchanged in remission and active stages. In addition, Iizuka et al [ 22 ] identified BJA during the remission stage in the stomach of a CD patient receiving an elemental diet. Moreover, Watari et al [ 8 ] observed 24 CD patients who underwent EGD, and found that 7 patients did not show BJA during their initial EGD, but that 2 of the patients exhibited BJA during their second EGD examination.…”
Section: Discussionmentioning
confidence: 99%